Family Support and Self Efficacy of Type 2 Diabetes Patients at Puskesmas Sangkrah : Dukungan Keluarga dan Self Efficacy Penderita DM Tipe 2 di Puskesmas Sangkrah - Wijaya, Chayanita Sekar; Wijayanti, Anisa Catur; Maulita, Nur Riqqah (Politeknik Harapan Bangsa Surakarta, 2024)
Non-Communicable Diseases (NCDs) have become one of the major health challenges worldwide, including in Indonesia. One of the main factors driving the increase in NCD cases in Indonesia is the shift towards increasingly unhealthy lifestyles among the population. Type 2 Diabetes Mellitus (Type 2 DM) is one of the most common types of NCDs currently found in Indonesia. This study aims to analyze the relationship between family support and self-efficacy in Type 2 DM patients at the Sangkrah Community Health Center. This research employs a quantitative design with an analytical observational cross-sectional approach. The study population consisted of Type 2 DM patients at the Sangkrah Community Health Center, with a sample size of 125 respondents obtained using the simple random sampling technique. Data analysis was conducted using the Chi-square statistical test. The results showed a significant relationship between family support and self-efficacy in Type 2 DM patients (p-value = 0.000; <0.05). Therefore, further research is needed to explore the relationship between family support and the occurrence of diabetes distress in Type 2 DM patients.